STRATEGIES TO DEVELOP FOOD CROP COMMODITY TO IMPROVE THE PROSPERITY OF RURAL FARMERS IN GR0BOGAN DISTRICT - Setiawan, Avi Budi; Prajanti, Sucihatiningsih Dian Wisika (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2016)
The policy strategy to develop the agricultural sector in Indonesia is important to be arranged as agriculture has various problems and needs a comprehensive policy. Many districts in Central Java are dominated by agriculture sector where agricultural Â becomes the basis for the economy. The agricultural sector therefore provides significant contribution towards economic structure and commoditiesâ€™ production. In terms of commodity, corn is the second biggest agricultural commodity after paddy in Grobogan district in Central Java, reflected by a huge demand of corn in the market. The strategy to develop corn farming in Grobogan district therefore needs to be dealt with various criteria and alternatives. This study will consider several aspects which have an important role in agricultural sector as strategies to develop food crop particularly corn commodity to improve the farmersâ€™ prosperity in Grobogan.